Coetzee in/and Afrikaans - Barnard, Rita (Journal of literary studies (Pretoria, South Africa), 2009)
This article investigates Coetzee's complex attitudes towards the Afrikaans language, and, by extension, his views on language, translation, and the potential and performative subject positions, or "fictions of the"-enacted in and determined by a given language. It reflects on relevant passages from Coetzee's criticism (including "Achterberg's 'Ballade van de Gasfitter'", "Emerging from Censorship", "What is a Classic?", and "He and His Man") and fiction (including In the Heart of the Country, Boyhood, Youth and Diary of a Bad Year). Partly concerned with the (auto)biographical, this essay also explores the idea of embarrassment (rather than the more frequently discussed shame) as a key affect in Coetzee's oeuvre.